KOMPARASI POLITICAL CAMPAIGN STRATEGIES: CALEG PETAHANA VIS A VIS CALEG PENDATANG (Studi Kasus Pemilihan Legislatif Kabupaten Kendal Tahun 2019) - Faizal Yafi Ananta; budi - setiyono (Journal of Politic and Government Studies, 2021)
Legislative elections are at stake for every candidate who takes part in the contestation. Competition for seats is followed by incumbent candidates or candidates as well as newcomers. This research is about how the incumbent's strategy to retain seats and newcomers to win seats. What is the difference in their strategy. Qualitative research methods, research informants are two incumbents and two newcomers who won seats in the Kendal Regency DPRD in the 2019 Election. Data collection uses interviews and documentation studies, and data analysis goes through the stages of data display, data reduction, and drawing conclusions. The results showed that there was no significant difference between incumbent and newcomer strategies. However, newcomers find it more difficult to campaign because segmentation and targeting only depend on the proximity of their background, while the incumbents are facilitated by the presence of a successful team that has been with them for a long time. In terms of the use of campaign media and their approach, there was no difference, namely they both used direct communication